Anthropometrical measurements and maternal visceral fat during first half of pregnancy: a cross-sectional survey - Daniela Cortés Kretzer; Salete Matos; Lisia Von Diemen; José Antônio de Azevedo Magalhães; Alice Carvalhal Schöffel; Marcelo Zubaran Goldani; Alexandre da Silva Rocha; Juliana Rombaldi Bernardi (BMC, 2020)
Abstract Background Determining anthropometric measures that indicate different fat deposits can be useful to predict metabolic risk and set specific treatment goals, reducing negative consequences for maternal and fetal health. In cases where pre-gestational weight measure and subsequent body mass index (BMI) values cannot be determined, other anthropometric measurements may be ideal for measuring the nutritional status of pregnant women, especially in low- and middle-income countries. This study aims to identify which anthropometric measurements correlate better with the maternal fat deposits measured by ultrasound. Methods A cross-sectional study was conducted with pregnant women from the city of Porto Alegre (city), capital of Rio Grande do Sul (state), southern Brazil, from October 2016 until January 2018. Anthropometrical variables (weight, height, mid-upper arm circumference [MUAC], circumferences of calf and neck and triceps skinfolds [TSF] and subscapular skinfolds [SBSF]), and ultrasound variables (visceral adipose tissue [VAT] and total adipose tissue [TAT]) were collected. To verify the correlation of anthropometric and ultrasound measurements, a non-adjusted and adjusted Spearman correlation was used. The study was approved by the ethics committees. Results The age median of the 149 pregnant women was 25 years [21-31], pre-pregnancy BMI was 26.22 kg/m² [22.16-31.21] and gestational age was 16.2 weeks [13.05-18.10]. The best measurements correlated with VAT and TAT were MUAC and SBSF, both of which showed a higher correlation than pre-pregnancy BMI. Conclusions It is possible to provide a practical and reliable estimate of VAT and TAT from the anthropometric evaluation (MUAC or SBSF) that is low cost, efficient and replicable in an outpatient clinic environment, especially in low- and middle-income countries.